The city - Weber, Max (Free Press, 1958)
Weber argues that the development of cities in European culture (Occidental cities) as an autonomous associations with its own municipal officials was influenced by such factors as: the religion of Christianity. the privileged legal position of the citizens (based upon citizen's obligation for military service). the decline of religious sanctions of kinship solidarity that facilitated creation of unified urban community.